Current and future therapies for advanced pancreatic cancer. Issue 1 (7th June 2017) - Gupta, Rohan; Amanam, Idoroenyi; Chung, Vincent
Abstract : Pancreatic cancer remains a deadly disease with a 5‐year survival rate of only 8%. Even after surgical resection, most patients have recurrence of their cancer. Over the last 10 years, improvements in chemotherapy regimens led to a doubling in median overall survival. Here we review the management of advanced pancreatic cancer and highlight vaccine therapy as a novel modality of treatment.